The augmented newsbeat: spatial structuring in a Twitterized news ecosystem. (January 2015) - Revers, Matthias
This article deals with the intertwining of digital and nondigital spaces of news reporting. It focuses specifically on how Twitter affects spatial and temporal orderings of news ecosystems. At the New York state government, actors within the space permeate informational barriers through Twitter while enabling others to follow and engage in events from remote locations. The always-on mentality of tweeters not only blurs boundaries between work life and private life but also helps correspondents to get access to and pass on information instantly, as well as to better anticipate events. The proliferation of digital spaces enhances awareness of nondigital spaces but requires coordination between the two. This paper is based on over two years of field research, involving observation, interviews, digital ethnography of the state house twitterverse and content analysis of journalists' tweets during the same-sex marriage debate.